2008
DOI: 10.1007/s00232-008-9120-x
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone Modulates Insulin-Induced Plasma Membrane Area Changes in Single 3T3-L1 Adipocytes

Abstract: In this study we hypothesized that rosiglitazone, an antidiabetic high-affinity agonist for the peroxisome proliferator-activated receptor gamma, affects the plasma membrane (PM) turnover in single 3T3-L1 adipocytes. To study the PM turnover, the patch-clamp electrophysiological method was used to measure changes in membrane capacitance (Cm), a parameter linearly related to the PM area. Microscopy results show that the presence of rosiglitazone in the differentiating medium significantly increased the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
9
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 40 publications
6
9
0
Order By: Relevance
“…Furthermore, adipocyte differentiation leads to the enhanced expression of adipocyte-specific genes, such as GLUT4 and insulin receptor substrate-1 (IRS-1), which are important components of the insulin receptor signaltransduction pathway (Ntambi and Young-Chuel, 2000;Okuno et al, 1998;White and Kahn, 1994;Wu et al, 1998). It was shown that the treatment of 3T3-L1 adipocytes with Rosi during differentiation results in the accumulation of GLUT4 at the plasma membrane surface (Martinez et al, 2010), which is consistent with the concept that TZDs regulate membrane dynamics (Velebit et al, 2008). However, the mechanism by which Rosi affects the increased density of GLUT4 at the plasma membrane remains unclear.…”
Section: Introductionsupporting
confidence: 66%
See 4 more Smart Citations
“…Furthermore, adipocyte differentiation leads to the enhanced expression of adipocyte-specific genes, such as GLUT4 and insulin receptor substrate-1 (IRS-1), which are important components of the insulin receptor signaltransduction pathway (Ntambi and Young-Chuel, 2000;Okuno et al, 1998;White and Kahn, 1994;Wu et al, 1998). It was shown that the treatment of 3T3-L1 adipocytes with Rosi during differentiation results in the accumulation of GLUT4 at the plasma membrane surface (Martinez et al, 2010), which is consistent with the concept that TZDs regulate membrane dynamics (Velebit et al, 2008). However, the mechanism by which Rosi affects the increased density of GLUT4 at the plasma membrane remains unclear.…”
Section: Introductionsupporting
confidence: 66%
“…However, the mechanism by which Rosi affects the increased density of GLUT4 at the plasma membrane remains unclear. It has been shown that insulin induces an increase in net changes of plasma membrane surface area of single 3T3-L1 cells by increasing the rate of exocytosis, via phosphatidylinositol 3-kinase, as in the case of insulin-induced GLUT4 translocation (Velebit et al, 2008), consistent with insulin-induced surface area measurements in adipocytes (Chowdhury et al, 2002(Chowdhury et al, , 2005. Interestingly, the pretreatment of 3T3-L1 cells with Rosi significantly attenuated the insulin-induced increase in membrane area (Velebit et al, 2008), which could be due to a simultaneous insulininduced increase in exo-and endocytosis of Rosi-pretreated cells.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations